Variances in rateable values in rating practice in Zambia: the role of mental models in value assessment. (3rd May 2016) - Munshifwa, Ephraim K.; Jain, Niraj; Kaunda, Busiku S.; Masiba, Lilias; Lungu, Jimmy; Chunda-Mwango, Nelly; Mushinge, Anthony; Ngoma, Wilson
Abstract: Rating valuation is an essential process for local government taxation and revenue generation in Zambia. However, preliminary evidence indicates that the assessment of rateable value is problematic as the same statutory valuation process may lead to different value outcomes. This is especially evident when valuations are undertaken by public valuation surveyors on one side and private valuation surveyors on the other. This has resulted in disagreements in Rating Tribunal hearings at which private valuation surveyors represent the objectors. This paper questions why such differences arise. The paper finds that, besides information factors, a major cause is valuation surveyor-specific factors which, among others, include adoption of different methods and viewpoints. Therefore, the question arises: why do valuation surveyors have different viewpoints or "mental models" if the whole process is specified in the Rating Act of 1997? The study concludes that the Rating Act of 1997 is insufficiently specific concerning the actual calculation of the rateable value, leaving the interpretation of value to individual valuation surveyors. The paper argues that the explanation for differences in values can be found in understanding the "mental models" of valuation surveyors, hence going beyond conventional explanations.